Brothers increase women's gender conformity - Anne Ardila Brenøe (University of Zurich, Department of Economics, 2021)
I examine how one central aspect of the family environment - sibling sex composition - affects women's gender conformity. Using Danish administrative data, I causally estimate the effect of having a second-born brother relative to a sister for first-born women. I show that women with a brother acquire more traditional gender roles, as measured through their choice of occupation and partner. This results in a stronger response to motherhood in labor market outcomes. As a relevant mechanism, I provide evidence of increased gender-specialized parenting in families with mixed-sex children. Finally, I find persistent effects to the next generation of girls.
Keywords: J12; J13; J16; J22; J24; J31; 330; Gender norms; gender conformity; sibling sex; occupational choice; motherhood